Double process of inclusion of women in cash crop: the case of cotton in the north of Ivory Coast - Moussa, SangarÃƒÂ© (Social Science Learning Education Journal, 2016)
The Ivorian government has popularized the cultivation of cotton in the north of Ivory Coast in order to reduce rural-urban migration, poverty, etc. Thus, the cotton program should involve all social categories (men, women, and youth) to achieve this ambitious objective of the state. But after more than three decades of cotton popularization, the reality in the field shows that, although women are strongly present at the production line, they are almost absents at marketing level. Without takingÂ intoÂ accountÂ that, they rarely leave the production sphere to become farm managers. However, this culture has long been